Diazoxide is a powerful cardioprotectant but is not feasible in a realistic infarct scenario - Kleinbongard, Petra; Lieder, Helmut; Skyschally, Andreas; Heusch, Gerd (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Diazoxide is a powerful cardioprotective agent which activates mitochondrial ATP-dependent K-channels and stimulates mitochondrial respiration. Diazoxide reduced infarct size in isolated rodent heart preparations and upon pretreatment in juvenile pigs with coronary occlusion/reperfusion. We aimed to study the use of diazoxide in a more realistic adult pig model of reperfused acute myocardial infarction when diazoxide was administered just before reperfusion. Methods and Results: In a first approach, we pretreated anaesthetised adult Göttingen minipigs with 7 mg kg-1 diazoxide (n=5) or placebo (n=5) intravenously over 10 min and subjected them to 60 min coronary occlusion and 180 min reperfusion; blood pressure was maintained by use of an aortic snare. Primary endpoint was infarct size (triphenyl tetrazolium chloride staining) as a fraction of area at risk; no-reflow area (thioflavin-S staining) was a secondary endpoint. In a second approach, diazoxide (n=5) was given from 50 to 60 min coronary occlusion, and blood pressure was not maintained. There was a significant reduction in infarct size (22±11% of area at risk with diazoxide pretreatment vs. 47±11% with placebo) and area of no-reflow (14±14% of infarct size with diazoxide pretreatment vs. 46±20% with placebo). With diazoxide from 50 to 60 min coronary occlusion, however, there was marked hypotension and infarct size (44±7%) and area of no-reflow were not reduced (35±25%). Conclusions: Cardioprotection by diazoxide pretreatment was confirmed in adult pigs with reperfused acute myocardial infarction, but is not feasible when administered in a more realistic scenario before reperfusion and causing hypotension.